Fractal carbon nanotube fibers with mesoporous crystalline structure. (October 2017) - Yue, H.; Reguero, V.; Senokos, E.; Monreal-Bernal, A.; Mas, B.; Fernández-Blázquez, J.P.; Marcilla, R.; Vilatela, J.J.
Abstract: Macroscopic fibres of carbon nanotubes are hierarchical structures combining long building blocks preferentially oriented along the fibre axis and a large porosity arising from the imperfect packing of bundles. Synchrotron small-angle X-ray scattering (SAXS) measurements show that such structure is a surface fractal with fractal dimension ( D s ) of 2.5 for MWCNT fibres and 2.8 for SWCNT fibres. N2 adsorption measurements give similar values of 2.54 and 2.50, respectively. The fractal dimension and deviation from Porod's law are related to density fluctuations associated with the wide distribution of separations between CNTs. These fluctuations are also evident as diffuse wide-angle X-ray scattering (WAXS) from CNTs at distances above turbostratic separation. The structure of CNT fibres produced at different draw ratios is compared in terms of degree of orientation and characteristic lengths parallel and perpendicular to the fibre. Drawing not only increases alignment but also the fraction of graphitic planes forming coherent domains capable of taking part in stress transfer by shear; thus increasing both tensile modulus and strength. The invariant-normalized intensity of the (002) equatorial reflection thus takes the form of a degree of crystallinity closely related to tensile properties. Graphical abstract: Macroscopic fiber assemblies of carbon nanotubes have a fractal network structure comprising a large mesoporosity coexisting with large oriented crystalline domains. Structure-properties are thus extracted from gas adsorption studies as well as WAXS/SAXS.